Health literacy program among the elderly with hypertension: a systematic review: 10.55131/jphd/2024/220325 - Onprasonk, Suwattana; Kannika Trinnawoottipong,; Sarach Buntrai, (Journal of Public Health and Development, 2024)
Health literacy programs (HLP) have been recognized as key factors in promoting health and in changing caregiving behaviors for older adults with hypertension, which have resulted in quality of life and continued good health. This systematic review was conducted with the aim of summarizing the effects of Health literacy programs (HLP) among the elderly with hypertension. From January 1, 2013, to December 31, 2022, the formulation of research questions was based on PICO and utilized a combination of the Boolean operators (AND or OR). The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach was used to choose the studies. The inclusion criteria, data extraction, and bias risk assessment screening were carried out independently by two reviewers. A total of eight papers were found to meet the criteria for review. The intervention exhibited notable variations both in terms of the quantity and the durations of the sessions. Nevertheless, the content remained predominantly similar, with a primary emphasis on health literacy. The studies, which had employed group-based interventions or had used a face-to-face individual approach, had been implemented in clinical settings or within communities. All the articles had used a combination of didactics and facilitation. However, the findings were not determined to be consistent across all studies. The patterns of enhancing HL among the elderly with hypertension are becoming increasingly important, and can, thereby, contribute to more efficiently controlling hypertension levels.